Superconvergence of Tetrahedral Quadratic Finite Elements (Journal of Computational Mathematics, 2018)
For a model elliptic boundary value problem we will prove that on strongly regular families of uniform tetrahedral partitions of a pohyhedral domain, the gradient of the quadratic finite element approximation is superclose to the gradient of the quadratic Lagrange interpolant of the exact solution. This supercloseness will be used to construct a post-processing that increases the order of approximation to the gradient in the global $L^2$-norm.
Keywords: Tetrahedron; Superconvergence; Supercloseness; Post-processing; Gauss points.